Adverse reproductive outcomes in women who subsequently develop rheumatoid arthritis. Issue 12 (December 1988) - Silman, A J; Roman, E; Beral, V; Brown, A
Abstract : The rates of adverse reproductive outcomes in 40 women with rheumatoid arthritis (RA) were compared with 67 of their unaffected female relatives. All women were aged between 35 and 65 years at the time of inquiry. Seven of the women with RA reported a perinatal death (six stillbirths, one early neonatal death) compared with one women in the unaffected group: estimated age adjusted relative risk (R) = 12.4, 95% confidence interval (95% CI) 1.6-91.1. The rate of spontaneous abortions was, however, not significantly different between the two groups (R = 1.2, 95% CI 0.5-2.9). All the perinatal deaths occurred before clinical disease onset in the women with RA. It is possible that in these two groups of women with a similar genetic background perinatal loss may be related, at least in part, to disease expression.